Pengaruh Kualitas Pelayanan Publik terhadap Tingkat Kepuasan dan Kepercayaan Masyarakat di Sekretariat Daerah Kota Surakarta - Nurmalasari, Ines (JI@P, 2025)
Abstract of the research "The Influence of Public Service Quality on the Level of Public Satisfaction and Trust in the Regional Secretariat of Surakarta City." as follows : Quality public services are a measure of the government's success in meeting the needs of the community. Success in improving the quality of public services at the Surakarta City Regional Secretariat can be measured through the level of satisfaction and trust in the agency. This study aims to determine the effect of the quality of public services on the level of public satisfaction at the Surakarta City Regional Secretariat. In this study, the theory according to Zeithaml, Parasuraman was used to measure the theory of public service quality and the level of public satisfaction with 5 dimensions namely tangible, reliability, responsiveness, assurance, dan emphaty, while the theory according to Gefen et al., in Setiawan & Achyar was used to measure public trust with 2 dimensions namely transparency dan integrity. The research method uses a quantitative approach through a survey with a Likert scale measurement, a sample of 80 respondents. Data collection techniques through questionnaires, unstructured interviews, and documentation. The data analysis techniques include Descriptive Analysis, Validity Test, Reliability Test, Normality Test, Linearity Test, Simple Linear Regression Test, T Test, Determination Coefficient Test. The results of the T-test study show that the influence of the quality of public services on the level of public satisfaction obtained a calculated t value (6.882) which is greater than the t table value (1.991). This can be concluded that the quality of public services has a significant influence on the level of public satisfaction, while the influence of the quality of public services on public trust obtained a calculated t value (1.025) which is smaller than the t table value (1.991). This can be concluded that the quality of public services does not have a significant influence on public trust. The Determination Coefficient Test shows that the R-Square determination coefficient value for the public service quality and public satisfaction level variables is (0.374), which means that 37.4% of the variation in the public satisfaction level variable has been explained by the public service quality variable, while for the public service quality and public trust variables it is (0.013), which means that 1.3% of the variation in the public trust variable is explained by the public service quality variable. Keywords: Quality of Public Services, Level of Public Satisfaction, Trust.